2021
DOI: 10.1108/jiabr-12-2019-0226
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of technical efficiency of Islamic banks in GCC countries

Abstract: Purpose This study aims to discuss the determinants of Islamic banks’ efficiency. It tries to explore the source of Islamic banks’ inefficiencies to propose solutions to guarantee an acceptable level of technical efficiency of such banks in Gulf Cooperation Council (GCC) countries. Design/methodology/approach To achieve this objective, the authors use a parametric approach, especially, the stochastic frontier approach, using production function and panel data analysis. The authors apply a package Frontier 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…e interrelationship between high-efficiency scores, adequate managerial processes, and good corporate governance practices are likewise examined [20,[25][26][27][28]. is result is in contrast with that of Galoriotis et al [24] that management practices have a negative effect on efficiency but consistent with Ullah [16] that corporate governance has a positive effect on cost efficiency and Mohamed et al [29] that managerial staff education has a negative effect on inefficiency. Akber and Dey [44] showed that conventional banks have better management and asset quality compared with Islamic banks.…”
Section: Linear Regression With Stepwise Methods For Islamic Banksmentioning
confidence: 96%
See 1 more Smart Citation
“…e interrelationship between high-efficiency scores, adequate managerial processes, and good corporate governance practices are likewise examined [20,[25][26][27][28]. is result is in contrast with that of Galoriotis et al [24] that management practices have a negative effect on efficiency but consistent with Ullah [16] that corporate governance has a positive effect on cost efficiency and Mohamed et al [29] that managerial staff education has a negative effect on inefficiency. Akber and Dey [44] showed that conventional banks have better management and asset quality compared with Islamic banks.…”
Section: Linear Regression With Stepwise Methods For Islamic Banksmentioning
confidence: 96%
“…e interrelationship between high-efficiency scores, adequate management, and good corporate governance practices has been investigated [25][26][27][28]. According to Mohamed et al [29], the education of managerial staff is negatively associated with inefficiency, that is, efficiency increases as the number of Shariah experts in banks management increases.…”
Section: Key Determinants Of Efficiency Several Scholars Study the Im...mentioning
confidence: 99%
“…Moreover, this issue remains largely unexplored in the context of GCC countries. In particular, there is a limited number of studies (Mohamed et al, 2021; Saif‐Alyousfi & Saha, 2021; Saw et al, 2020) that investigate the diverse impact of corruption on bank efficiency with a theoretical perspective. The primary objective of this paper is to provide empirical evidence on the impact of corruption on the efficiency of the GCC banking sector.…”
Section: Introductionmentioning
confidence: 99%